Updates in Long-term Maternal and Fetal Adverse Effects of Gestational Diabetes Mellitus. Issue 2 (15th October 2019) - Shou, Chong; Wei, Yu-Mei; Wang, Chen; Yang, Hui-Xia
Abstract : Abstract: Gestational diabetes mellitus (GDM) is associated with long-term maternal and fetal adverse outcomes. Recent evidences suggest GDM increases long-term maternal cardiovascular disease, chronic kidney disease, and cancer risks. Maternal hyperglycemia is associated with offspring obesity, overweight, insulin resistance, and neurocognitive development. It remains unclear whether treating mild GDM would reduce long-term maternal and fetal adverse effects.